ARRESTED OROGENIC DEVELOPMENT: ECLOGITIZATION, DELAMINATION,AND TECTONIC COLLAPSE - Leech M.L. (My University, 2001)
Fluids are key in the process of eclogitization and delamination of crustal roots in collisional orogens, and this process is not solely constrained by pressure–temperature conditions. Partially eclogitized amphibolites, gabbros, and granulites from the Western Gneiss Region of Norway, the Marun-Keu Complex in the polar Urals, and the Dabie-Sulu belt in China demonstrate that fluid is required for complete eclogitization. Conventionally, orogeny proceeds in a cycle that progresses from collision and uplift, to metamorphism and delamination of the crustal root, to completion when the orogen undergoes tectonic collapse. The south Ural Mountains and the southern Trans-Hudson orogen are type examples of arrested orogenic development in which delamination and post-orogenic extensional collapse have not occurred. Because the eclogitization of crustal roots leads to delamination and tectonic collapse of orogens, it is likely that the base of the Uralian crust has not undergone major eclogitization and therefore is under fluid-absent conditions. The lack of post-orogenic tectonic collapse and extensional faulting of some ultrahigh-pressure (UHP) orogens has major implications for exhumation models of UHP metamorphic terranes. Extension on the Main Uralian fault in the south Urals did not play a important role in the exhumation of the UHP Maksyutov Complex; the dominance of quartzofeldspathic rock types in the Maksyutov Complex and widespread retrograde metamorphism indicate that buoyancy rather than extensional faulting was likely the dominant cause of exhumation in the south Urals.
Keywords: eclogite facies; orogeny; Urals; Hudsonian Orogeny